From smart growth to European spatial planning: a new paradigm for EU cohesion policy post-2020 - Medeiros, Eduardo (2018)
Formally initiated in 1989, European Union (EU) cohesion policy (ECP) has since passed through a series of metamorphoses, along its five programming periods, while becoming the most financed EU policy. As its name indicates, its initial goals were earmarked for promoting economic and social cohesion, following the intentions expressed in the Single European Act. Since then, from a policy strategy intervention point of view, ECP has shifted into a financial tool to promote investment for growth and jobs. In the meantime, European spatial planning (ESP), which had its debating pinnacle with the release of the European Spatial Development Perspective, by 1999, has declined in interest and narrowed into a novel notion of Territorial Cohesion. In this challenging context, this article analyses the implementation and main impacts of ECP and proposes a new strategic paradigm, built around a novel ‘ESP’ vision, backed by the main pillars and dimensions of territorial development and cohesion. More particularly, we suggest that the current rationale for a smart, sustainable and inclusive growth could instead fuel an alternative strategic design based on a cohesive and sustainable development vision: green economy, balanced territory, good governance and social cohesion.